Reduction of Pain and Depression in Occlusal Splint-Based Treatment for TMD is Accompanied with Increase in Urinary Serotonin - M.B. Nunes; J. Oliveira; R. Brito (Journal of Basic & Applied Sciences, 2014)
The aim of this study was to assess the parallel effects of an occlusal splint-based intervention for TMD on urinary serotonin levels, depression and pain. Previous RCT studies have shown that occlusal splint-based treatment reduce pain and depression, but have not measured serotonin. 15 patients (four males and 11 females) completed an intervention protocol with a silicone dental splint for 60 days. Patients were assessed before and after treatment for urinary serotonin levels, TMD-related pain and depression symptoms (self-reports). Results showed a significant increase in urinary serotonin levels between the two assessments along with a reduction in pain and depression. Overall results suggest that the positive effects of occlusal-based treatment on physical and mental health could be related to increases in serotonin levels.